Comparison of Thai older patients’ wishes and nurses’ perceptions regarding end-of-life care - Manjavong, Manchumad (Nursing ethics, 2019)
Background:Achieving a “good death” is a major goal of palliative care. Nurses play a key role in the end-of-life care of older patients. Understanding the perceptions of both older patients and nurses in this area could help improve care during this period.Objectives:To examine and compare the preferences and perceptions of older patients and nurses with regard to what they feel constitutes a “good death.”Research design:A cross-sectional study.Participants and research context:This study employed a self-report questionnaire that asked about various options for end-of-life care. It was distributed to older patients who attended the outpatient clinic of internal medicine and nurses who worked at two medical schools in Thailand from September 2017 to February 2018. Patients were asked to respond to the questions as if they were terminally ill, and nurses were asked to imagine how older patients would answer the questions.Ethical consideration:Approval from Institutional Review Board was obtained.Findings:A total of 608 patients and 665 nurses responded to the survey. Nurses agreed with concepts of palliative care, but they rated themselves as having poor knowledge. The patient respondents felt that it was most important that they receive the full truth about their illnesses (29.2%). The nurses thought the most important issue was relief of uncomfortable symptoms (25.2%). On seven out of the 13 questions, nurses overestimated the importance of the relevant issue to patients and underestimated the importance on one question (p < 0.05).Discussion:Both nurses and older patients signified concepts of palliative care, but nurses felt that they lacked adequate knowledge. Nurses estimated that patients would have positive attitudes toward autonomy and the closure of life affairs to a significantly greater degree than the patient respondents.Conclusions:We recommend that palliative care education be improved and that steps be taken to allow for more effective nurse–patient communication with regard to the patients’ end-of-life wishes.